Cetuximab-Associated Crescentic Diffuse Proliferative Glomerulonephritis. (16th November 2017) - Manthri, Sukesh; Bandaru, Sindhura; Chang, Anthony; Hudali, Tamer
Abstract : Cetuximab-induced nephrotoxicity is very rare, occurring in less than 1% of colorectal cancer patients and not defined in other populations. We report a rare case of crescentic diffuse proliferative glomerulonephritis (GN) that developed in close temporal association with cetuximab treatment. A 65-year-old female recently completed chemotherapy with cetuximab treatment for moderately differentiated oral squamous cell carcinoma. She was admitted with acute renal failure and nephrotic-range proteinuria. Laboratory data showed serum creatinine of 6.6 mg/dl and urinalysis showed proteinuria, moderate hemoglobinuria, hyaline casts (41/LPF), WBC (28/HPF), and RBC (81/HPF). Serologic studies were negative for ANA, anti-GBM, ANCA, hepatitis B, and hepatitis C. Serum C3 and C4 level were normal. Renal biopsy showed crescentic diffuse proliferative GN with focal features of thrombotic microangiopathy. Patient was started on cyclophosphamide and steroids. Her renal function did not improve on day 8 and she was started on hemodialysis. Previous reports suggest that EGFR-targeting medications can possibly trigger or exacerbate an IgA-mediated glomerular process leading to renal failure. This case suggests that cetuximab therapy may have triggered or exacerbated a severe glomerular injury with an unfavorable outcome. Treating physicians should maintain a high degree of caution and monitor renal function in patients on EGFR inhibitors.